Implementasi Kebijakan Pengendalian Banjir dan Genangan Melalui Rumah Pompa oleh Dinas Sumber Daya Air dan Bina Marga Kota Surabaya - Bethania Anindhita Putri Wahyudi; Suci Megawati; Indah Prabawati; M. Noer Falaq Al Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of flood and inundation control policy through pump houses managed by the Surabaya City Water Resources and Highways Agency (DSDABM), focusing on the Ketintang area in South Surabaya. A descriptive qualitative method was applied, combining interviews, observation, and documentation, and the data were analyzed through the four indicators of George C. Edward III's policy implementation model, namely communication, resources, disposition, and bureaucratic structure. The findings show that technical-operational communication among DSDABM, the meteorological agency, and pump house operators runs relatively well, while formal policy communication is still hindered because the local flood regulation has not yet been legally enacted. In terms of resources, budget limitations, a shortage of field operators, and incomplete security facilities at pump houses remain persistent obstacles. The disposition of policy implementers is comparatively strong, yet public participation in maintaining drainage channels remains low. The bureaucratic structure at the technical level, organized through a zonal system, appears fairly decentralized, whereas coordination between DSDABM and the city council in drafting the flood regulation has not produced a clear timeline.